Modelling of work of the rotor-type blade pump with revolving stator - Horodetskyy, Ivan; Dmytriv, V.T.; Dmytriv, I.V.; Lanets, O.S. (Zielona Góra: Uniwersytet Zielonogórski)
In the article, the analytical dependences of modelling the cell cross-sectional area between two adjacent blades of a rotary blade pump and capacity for a pump with fixed and rotating stators are given, and analytical dependences are derived to model the power necessary to overcome the friction forces of the blades.
Keywords: rotor-type pump; stator; capacity; analytical models; speed; acceleration